Populismo conservador e agendas anti-LGBT no Brasil e na Rússia: um estudo comparado - Diogo Gonçalves Alvares (2022)
This master’s thesis aims to conduct a comparative study on the relationship between conservative populism and anti-LGBT agendas in the context of the governments of Vladimir Putin in Russia and Jair Bolsonaro in Brazil. This objective came about from the observation that, among the researches on populism, there is still a need for comparative analyses focused on a characteristic observed in several populist projects: the opposition to rights related to sexual and gender diversity. To achieve this objective, the thesis firstly presents a critical theoretical analysis concerning the methodological issue in comparative law. In this analysis, the comparative method adopted in the research, namely, the culturalist approach conceived by Pierre Legrand, is presented. The following chapter, based on the studies of Jan-Werner Müller, Tom Ginsburg, and Aziz Huq, investigates the elements that characterize populism and why this phenomenon is related to the process of democratic erosion. In this part, it is also presented what configures a type of populism that is particularly problematic to LGBT rights: conservative populism. The research then focuses on several cases of conservative populism around the world and how anti-LGBT agendas are structured in these political projects. In this global panorama, it is possible to identify the cases of Vladimir Putin and Jair Bolsonaro and to analyse the construction of their anti-LGBT populist discourses and the translation – or attempted translation – of these discourses into normative measures. This final analysis considers theoretical and contextual factors presented throughout the thesis as well as the way this relationship between conservative populism and anti-LGBT agendas in Brazil and Russia is conditioned by the intensity of the democratic erosion in these two countries.